Penggunaan Model Pembelajaran ATM untuk Meningkatkan Keaktifan dan Hasil Belajar IPS - Ari Istiadi; Esti Setiawati (Proceedings Series on Social Sciences & Humanities, 2022)
The new archetype of Indonesian education has brought about a change in the position of teachers and students in teaching and learning activities. In the past, the teacher was the source of all information, but along with the development of science and technology, the teacher served as a facilitator, mentor and at the same time a learner. Meanwhile, students are no longer reminders of facts and principles but have the position of reviewers, problem-solvers, and strategy creators. One of the things that can be done to synergize the position of teachers and students in the millennial era is by using learning models that are in accordance with technological developments and integrated good character development. This article aims to describe the stages in using the ATM learning model (inviting, accompanying, and independent) in elementary schools in social studies learning. The purpose of implementing the ATM learning model is to determine the plan and implementation of learning, increase student activity, and increase student social studies learning outcomes in cognitive and psychomotor aspects. The application of this ATM learning model in cycle II was able to improve the results of teacher performance so that it could achieve the target of 100%. Then able to increase the activeness of students to reach the target of 83.33%. Student learning outcomes increased to reach the target of 87.50% both from the cognitive aspect and the aspect of skill performance presenting the results of the identification of the use of natural resources.